Carbapenem resistance shapes the population structure of Klebsiella pneumonia - Krestetska, Svitlana; Peretyatko, Olena; Sklyar, Nadia; Yagnuk, Yulya (Annals of Mechnikov's Institute, 2025)
Klebsiella pneumoniae (Kp) is an ubiquitous and highly versatile species from the family Enterobacteriaceae. Remarkable genetic and phenotypic plasticity determines its success in adapting to a wide range of environmental and host-associated niches (e.g., fresh and salt waterwater, soil, plants, insects, birds, and animals, including humans, where it usually persists as a gut commensal, but also can colonize other mucosal surfaces and skin). Certain lineages can cause severe invasive community-acquired (CA) infections, but the majority behave as a typical opportunistic pathogen, persistingasymptomatically till the moment of the host vulnerability. One of the most concerning aspects of Kp's recent evolution is its adaptation to the environment of healthcare facilities. The species is one of the major nosocomial pathogens, and the most frequent cause of neonatal sepsis worldwide. Distinguishing clinical feature of Kp infections is propensity for the development of bacteremia and metastatic spread to unusual and often multiple locations (e.g., hepatic, and non-hepatic abscesses, meningitis, endophthalmitis, necrotizing fasciitis, etc.). Despite such a prominent clinical relevance per se, Kp has been recognized as a global healthcare threat primarily due to its contribution to the current crisis of carbapenem resistance (CR). Certain epidemiologically successful lineages turned out to be incredibly effective in the accumulation, maintenance, and spread of resistance-associated mobile genetic elements (rMGEs) among other clinically relevant Gram-negative organisms. The aggregation of numerous resistance genes (including those, encoding ESBL's and/or carbapenemases) within a specific Kp genetic background has led to the emergence of global hospital outbreak CRKp clones, followed by multispecies outbreaks of difficult-to-treat CR healthcare associated infections (HAI) worldwide. Recent surveillance efforts and molecular epidemiology studies demonstrate a complex population structure of Kp, characterized by hundreds of deeply branching phylogenetic lineages. These lineages exhibit significant differences in the distribution of genes conferring antibiotic resistance and virulence, as well as variable transmissibility within the hospital environment. This review focuses on understanding the evolution of clinically relevant genetic variants of CRKp, which is crucial for the development of effective control strategies.